Designing an ICT-Integrated Learning Program Strategy - Ratsimandisa Haritiana Zo; Rafatro Robijaona Baholintsoa (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2025)
This study examines the obstacles and opportunities in creating an ICT-integrated learning strategy at Ambararatabe General High School in Madagascar. Several interconnected factors hinder optimal ICT integration: limited teacher expertise, a scarcity of resources, and logistical challenges like unreliable transportation and communication infrastructure. A SWOT analysis, incorporating the PESTEL framework, shows that while political stability and digitization offer opportunities, economic disparities, insecurity, and insufficient ICT proficiency among students and teachers pose threats. The study explores the institution's micro-environment, highlighting collaborations with the Ministry of Education, UNICEF, and UNESCO, which provide crucial support. However, many students lack technology access and proficiency, a divide worsened by socio-economic factors. School procedures aim to raise parental awareness and support struggling students, emphasizing the need for community and institutional engagement. The findings suggest a multi-faceted approach is needed, including investments in infrastructure, teacher training, and interventions to address socio-economic barriers. Emphasizing ICT's potential to reduce inequalities and promote sustainable development, the study advocates for policies that foster digital literacy, ensure equitable access to technology, and enhance education to prepare students for a digital world.